The Impact of Senna Siamea (Lam) leaves extracts on 2, 2-Dichlorovinyldimethyl Phosphate Induced Brain Oxidative Stress in Wistar Albino Rats (Global Journal of Medical Research, 2021)
Organophosphate compounds have been a common source of mortality in recent times. A typical example is dichlorvos [2, 2-Dichlorovinyldimethylphosphate (DDVP)]; an important agricultural pesticide. This study sought to investigate the phytochemical screening, invitro antioxidant property of the leaf solvents extracts and ameliorating effects of Senna siameain DDVP-induced brain oxidative stress in Wistar rats. The aqueous, methanol and ethanol extracts of the leaves were obtained and analyzed for their in-vitro antioxidant parameters. Thirty-two healthy Wistar albino rats were grouped into eight of 4rats each weighing between 140-150g. The animals were orally administered with 6.6mg/kg body weight of DDVP except groups1 and 2 followed by treatments with the three solvents extracts respectively that lasted for four weeks.
Keywords: Senna siamea; brain toxicity; oxidative stress; antioxidant properties; #x3B3; -glutamyl transferase